2019
DOI: 10.7150/ijbs.33044
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Down-Regulation of Sirt 1 via DNA Methylation and Oxidative Stress Signaling Contributes to the Gestational Diabetes Mellitus-Induced Fetal Programming of Heart Ischemia-Sensitive Phenotype in Late Life

Abstract: Rationale: The incidence of gestational diabetes mellitus (GDM) is increasing worldwide. However, whether and how GDM exposure induces fetal programming of adult cardiac dysfunctional phenotype, especially the underlying epigenetic molecular mechanisms and theranostics remain unclear. To address this problem, we developed a late GDM rat model. Methods: Pregnant rats were made diabetic on day 12 of gestation by streptozotocin (STZ). Experiments were conducted in 6 weeks old offspring. Results: There were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 57 publications
2
40
0
1
Order By: Relevance
“…GDM is a heterogeneous multivariate pregnancy disease with complicated pathological mechanism. In addition to inflammatory reaction, IR and abnormality of lipid and glucose metabolism, GDM also involves DNA methylation and oxidative stress signal transduction that affect cardiac function (21). Statistics showed that the increase in the prevalence of GDM is global and 33.33% of GDM pregnant women will suffer from postpartum depression (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…GDM is a heterogeneous multivariate pregnancy disease with complicated pathological mechanism. In addition to inflammatory reaction, IR and abnormality of lipid and glucose metabolism, GDM also involves DNA methylation and oxidative stress signal transduction that affect cardiac function (21). Statistics showed that the increase in the prevalence of GDM is global and 33.33% of GDM pregnant women will suffer from postpartum depression (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…48 Our work also validates the previous findings that SIRT-1 is a key pathway affected by GDM. 49 Furthermore, we demonstrated in relevant in vitro models that FKBPL and SIRT-1 proteins are reduced in both the presence of hyperglycaemia and low oxygen tension that could have adverse effects on trophoblast function and placental development 31 .…”
Section: Discussionmentioning
confidence: 89%
“…The offspring rats (~3 month-old) were subjected to myocardial ischemia-reperfusion in vivo as described previously 22 . Briefly, rats were anesthetized with isoflurane (5% for induction, 3% for maintenance) (Vet ONE, USA) mixed with oxygen (2 L/min for induction, 1 L/min for maintenance) by inhalation and placed on the RoVent Jr. Small Animal Ventilator (Kent Scientific).…”
Section: Methodsmentioning
confidence: 99%